2013
DOI: 10.1093/intimm/dxt062
|View full text |Cite
|
Sign up to set email alerts
|

Tyk2 is a therapeutic target for psoriasis-like skin inflammation

Abstract: Tyrosine kinase 2 (Tyk2), a member of the Jak kinase family, mediates signals triggered by various cytokines, which are related to the pathogenesis of psoriasis. In this study, we investigated the role of Tyk2 in IL-23-induced psoriasis-like skin inflammation. Tyk2(-/-) mice when injected with IL-23 showed significantly reduced ear skin swelling with epidermal hyperplasia and inflammatory cell infiltration compared with wild-type mice. In addition, Tyk2 deficiency reduced production of pro-inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 52 publications
4
61
0
1
Order By: Relevance
“…3). Previous reports demonstrated a requirement of Tyk2 for fullfledged STAT3 activation upon inflammation for lymphoid tissues (4) and keratinocytes (5). As expected (8), the expression of the major STAT3-activating cytokines IL-6 and IL-22 was elevated during colitis, albeit with no genotype differences that could account for the impaired pY-STAT3 in Tyk2 2/2 mice (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…3). Previous reports demonstrated a requirement of Tyk2 for fullfledged STAT3 activation upon inflammation for lymphoid tissues (4) and keratinocytes (5). As expected (8), the expression of the major STAT3-activating cytokines IL-6 and IL-22 was elevated during colitis, albeit with no genotype differences that could account for the impaired pY-STAT3 in Tyk2 2/2 mice (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Genome-wide association studies identified Tyk2 as susceptibility locus for IBD in humans (41). During inflammation, Tyk2 2/2 mice show opposing phenotypes in that they are either protected from Th1-or Th17-driven diseases (4,5,42,43) or more prone to Th2-or Th9-dominated pathology (2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot show a significant difference between the groups this is still intriguing since TYK2 is part of the IL-23 pathway which seems preferentially involved in the severe psoriasis phenotype and inhibition of Tyk2 kinase activity lead to significantly reduced IL-23-induced skin inflammation and may be an effective therapeutic strategy for the treatment of psoriasis (Ishizaki et al, 2014;Liang et al, 2013).…”
Section: Discussionmentioning
confidence: 64%
“…13,14 The first TYK2 specific inhibitors have been recently developed and are considered as promising therapeutic agents for the treatment of inflammatory and autoimmune diseases. [15][16][17][18][19][20] Very recently, tumor cell-intrinsic TYK2 activity has been linked to the development of T cell acute lymphoblastic leukemia (T-ALL) and cutaneous T cell lymphoma development in humans. 21,22 Therefore, specific inhibition of TYK2 activity might be considered as a new therapeutic opportunity for some hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%